Determination of substrate log-normal distribution in the AZ91/SICP composite - J. Lelito; P. L. Żak; B. Gracz; M. Szucki; D. Kalisz; P. Malinowski; J. S. Suchy; W. K. Krajewski (Metalurgija, 2015)
The aim in this work is to develop a log-normal distribution of heterogeneous nucleation substrates for the composite based on AZ91 alloy reinforced by SiC particles. The computational algorithm allowing the restore of the nucleation substrates distribution was used. The experiment was performed for the AZ91 alloy containing 1 % wt. of SiC particles. Obtained from experiment, the grains density of magnesium primary phase and supercooling were used to algorithm as input data.